Determinants Affecting the Digital Payment System Adoption in India - Deepa Garg and Dr. Shalini Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This study explored the adoption of digital payment systems in India, highlighting the demographic characteristics and perceptions influencing consumer behavior. A survey of 150 respondents revealed a diverse sample, with a majority of participants being young, educated, and employed. The analysis indicates high awareness of digital payments, with 86.67% of respondents familiar with the systems. Mobile wallets and UPI emerged as the most popular methods, while 80% found digital payments easy to use. Trust and perceived usefulness were significant factors, with 86.67% believing in the reliability of these systems. Despite some security concerns, the overall sentiment remains positive, suggesting a promising trajectory for digital payment adoption. The study emphasizes the importance of expanding financial literacy programs, strengthening security measures, and enhancing user-centric design in digital payment applications. Additionally, leveraging social influence and government initiatives can further encourage the transition from cash to digital payments. The findings offer valuable insights for policymakers, financial institutions, and technology providers in fostering a more inclusive and secure digital payment ecosystem, ultimately contributing to economic growth and financial inclusion in India.